Pengaruh Ratio Overlap Sudu Terhadap Performa Turbin Air Poros Horizontal Savonius - rendi rendi (Proklamasi 45 University, 2023)
The Savonius air turbine has the ability to generate electricity from low-flow water sources and can be used in various types of water sources. However, the efficiency of this turbine is still low compared to other types of water turbines. Previous studies have shown that the overlap ratio of the blades can affect the turbine efficiency and power generated. Therefore, this study aims to investigate the effect of blade overlap ratio on the performance of the horizontal-axis Savonius water turbine. The purpose of this research is to study the influence of blade overlap ratio. It is hoped that the results of this study can be used as a reference in the production of horizontal-axis Savonius water turbines.